2020
DOI: 10.2174/1876402911666190603093550
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Transethosomes for Enhanced Transdermal Delivery of Propranolol Hydrochloride

Abstract: Objective: The objective of the present work was to develop transethosomes loaded with propranolol hydrochloride using Lipoid S100 as phospholipid, and oleic acid as permeation enhancer and evaluate them for prolonged release effect, in-vitro skin permeation, and in-vivo plasma concentration. Methods: Transethosomes loaded with propranolol hydrochloride were prepared by homogenization method. Furthermore, they were characterized by using Transmission Electron Microscopy (TEM), zeta sizer, Differential Scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Kumar and Utreja (2020) developed TEs gel using propranolol hydrochloride (PPLH), Lipoid S100 (phospholipid), and permeation enhancer (oleic acid). While using in‐vitro skin permeation study (Confocal Laser Scanning Microscopy—CLSM) and in vivo plasma concentration on Sprague‐Dawley rats, he established whether or not the drug is delivered in a sustained fashion.…”
Section: Research Based Consideration Of Tesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kumar and Utreja (2020) developed TEs gel using propranolol hydrochloride (PPLH), Lipoid S100 (phospholipid), and permeation enhancer (oleic acid). While using in‐vitro skin permeation study (Confocal Laser Scanning Microscopy—CLSM) and in vivo plasma concentration on Sprague‐Dawley rats, he established whether or not the drug is delivered in a sustained fashion.…”
Section: Research Based Consideration Of Tesmentioning
confidence: 99%
“…The authors reported in in‐vivo method exhibited that TEs successfully released the drug for up to 24 h, with a peak plasma concentration (C max ) of 93.83 ng/mL, which was significantly higher than the commercially available oral tablet of PPLH (45.63 ng/mL). In conclusion, the researcher concluded that the formulated TEs gel of PPLH could be a superior alternative to oral PPLH because it can circumvent the major drawbacks of oral PPLH especially the first‐pass metabolism effect, organ toxicity, and the need for frequent dosage (Kumar & Utreja, 2020). While using full factorial design, Albash et al (2019) formulated Olmesartan medoxomil (OLM) TEs by considering several surfactants (Tween 20 and 80; Span and 60; sodium deoxycholate at 5, 15 and 25 mg each) and in different phospholipid (Phospholipid at 75, 85, and 95 mg each) to surfactant ratios by employing thin‐film hydration method.…”
Section: Research Based Consideration Of Tesmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Kumar et al found that sustained release of drug can be achieved over 24 h. This can reduce dosing frequency which leads to better patient compliance. 58…”
Section: In Vitro Drug Release Studymentioning
confidence: 99%
“…Interestingly, various delivery systems were suggested to enhance PRO skin permeation, including polymeric film [ 60 ], iontophoresis [ 61 ], transethosomes [ 62 ], and nanoparticles [ 63 ]. Herein, PRO skin permeability was improved with the development of ufasomes (UFAs), which are non-phospholipid vesicles.…”
Section: Introductionmentioning
confidence: 99%